The Role of Collagenase Clostridium histolyticum in Dupuytren’s Disease: A Systematic Review - Moreira Sousa, Rui (2023)
Introduction: Dupuytren’s disease (DD) is a benign and progressive fibroproliferative disease that involves the palmar fascia, where collagenous cords form from the overlay of nodular fibrotic tissue. Clostridium histolyticum collagenase (CHC) is a minimally invasive option for the treatment of advanced DD. CHC allows collagen lysis, leading to the rupture of fibrous cords. This review aims to reflect on the existing scientific evidence about the role of CHC in the treatment of DD.Methods: The study presented is a systematic review. Authors followed PRISMA reporting guidelines. The search was performed using the following databases: PubMed, ClinicalTrials.gov and Cochrane Central Registry of Controlled Trials (CENTRAL). As inclusion criteria, randomized and non-randomized clinical trials and observational studies were considered. As an exclusion criterion, all studies not written in English were excluded. The primary outcome was efficacy, through reduced contracture or increased range of motion. Safety/adverse effects, degree of contracture recurrence and patient satisfaction with the application of this technique were considered secondary outcomes. All relevant articles were systematically reviewed by 2 reviewers.Results: The search resulted in 30 studies, 15 of which were selected by 2 independent reviewers. CHC therapy was shown to be superior in efficacy when compared to placebo and similar results when compared to surgical options. Regarding secondary outcomes, CHC therapy proved to be a safe treatment with a high patient satisfaction, with low recurrence rates and similar recurrence rates after surgical treatments with 5 years of follow-up.Conclusion: CHC has proven to be an effective and safe therapy in DD patients, as well as a non-invasive alternative to surgery.